2018
DOI: 10.36406/ijbam.v1i2.566
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Profitability On Stock Return With Inflation As A Moderating Variable

Abstract: Abstract—This study aims to analyze the effect of profitability on stock returns with inflation as a moderating variable. The variables tested in this research are profitability proxy for Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM), inflation and stock returns. The sample of this research uses 12 automotive companies and automotive components that consistently published financial statements in the Indonesia Stock Exchange period 2013-2017. Samples were taken by purposive sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
1
Order By: Relevance
“…(Sihombing and Sinaga 2020). Some research in the past have found Return on Equity to be positive and significant in affecting Stock Return (Allozi and Obeidat 2016) (Sihombing and Sinaga 2020), while others found a negative relationship instead (Banerjee 2019) (Sugito et al 2020). Some research also found a non-significant relationship instead (Aftab and Naseer 2016).…”
Section: Tinjauan Literaturmentioning
confidence: 98%
“…(Sihombing and Sinaga 2020). Some research in the past have found Return on Equity to be positive and significant in affecting Stock Return (Allozi and Obeidat 2016) (Sihombing and Sinaga 2020), while others found a negative relationship instead (Banerjee 2019) (Sugito et al 2020). Some research also found a non-significant relationship instead (Aftab and Naseer 2016).…”
Section: Tinjauan Literaturmentioning
confidence: 98%
“…Harga pasar adalah adalah harga yang dimuat dalam media massa seperti surat kabar, harga pasar adalah harga jual yang terjadi di antara investor satu dengan investor lainnya tanpa melibatkan penjamin emisi atau perusahaan penerbit. Harga pasar akan dibentuk oleh interaksi antara penjual dengan pembeli saham (Sugito et al, 2019).…”
Section: Harga Saham (Stock Price)unclassified